Evaluation of byproducts of Solanum tuberosum and Daucus carota by FES as an alternative in animal feed - Caro Cusba, Nidia Lorena; Saavedra Montañez, Gabriel Fernando; Borras Sandoval, Luis Miguel (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The growing demand for foods such as corn or soybeans has favored the implementation of biotechnologies through the use of agro-industrial waste in order to obtain alternative diets with high biological value. For this reason, the objective of this research was to develop a diet based on harvest by-products of potato Solanum tuberosum and carrot Daucus carota treated by Solid State Fermentation (FES). Postharvest quality analysis was carried out, subsequently, they were mixed in a proportion of 15% together with palm kernel (20%), wheat ceme (20%), soybean cake (10%), corn (10%), coffee husk (5%), molasses (4%) and additives such as vitamin premix (0.5%) and bacterial inoculant (0.5%). The prepared food was then subjected to FES and evaluated by compositional and microbiological analysis. Descriptive statistical analysis of the evaluated variables was performed and DM values ​​of 66.7%, humidity 33.3%, crude protein 19.4%, ash 5.21%, ether extract 6.35% and crude fiber 16,9% were obtained. The microbiological analysis determined that the aerobic mesophil count was exponentially higher at 48 hours compared to 72 hours (110.67 ± 23.44), no growth of molds and yeasts was observed at 48 hours and at 72 hours they were reported (14.67 CFU / g ± 5.03). It is concluded that by using FES the biological value of potatoes and carrots can be increased in a mixture with other raw materials to obtain diets intended for animal feed.